Analisis Bibliometrik Isu Kewarganegaraan Kontemporer: Radikalisme, Intoleransi, Korupsi, Disintegrasi Bangsa serta Pendekatan Solusinya - Pratama, Obib Madhandi; Habiba, Nur; Raisah Fathinah Kaltsum; Renita Apreli Yolanda (Yayasan Darussalam Bengkulu, 2025)
This research aims to identify keyword trends in articles published by other researchers that relate to the discussion topic of contemporary citizenship issues. The key issues highlighted in these articles include radicalism, intolerance, corruption, and national disintegration. Furthermore, solution approaches that can be applied to address these issues will also be discussed. The bibliometric analysis was conducted by searching for relevant articles using the Publish or Perish application, after which the article data was analyzed using VOSviewer. The results of this analysis are presented as a keyword network map. The study found 17 relevant articles containing 171 keywords, which were then narrowed down to the four most frequent keywords. By observing the relationship patterns of these keywords, we can conclude what constitutes contemporary citizenship issues.